Anticancer drug delivery systems based on inorganic nanocarriers with fluorescent tracers. Issue 3 (4th October 2017) - Fan, Jiangli; Wang, Suzhen; Sun, Wen; Guo, Shigang; Kang, Yao; Du, Jianjun; Peng, Xiaojun
Abstract : In recent years, anticancer nanomedicines have mainly been developed for chemotherapy and combination therapy in which the main contributing anticancer drugs are delivered by deliberately designed nano drug delivery systems (nano‐DDSs). Inorganic nanocarriers equipped with fluorescent tracers have become attractive tools to monitor the whole drug delivery and release processes. The fluorescence signal of tracers could be observed concomitantly with drug release, and thus, this strategy is of great benefit to evaluate the therapeutic effects of the nano‐DDSs. This review provides a brief overview about three inorganic nanocarriers for drug delivery, including mesoporous silica, Fe3 O4, and hydroxyapatite. We mainly discussed about their preparation processes, drug loading capacities, and the development of different fluorescent materials (fluorescent dyes, quantum dots, fluorescent macromolecules, and rare earth metals) hybridized to nanocarriers for real‐time monitoring of drug release both in vitro and in vivo. This review also provides some recommendations for more in‐depth research in future. © 2017 American Institute of Chemical Engineers AIChE J, 64: 835–859, 2018